2020
DOI: 10.1101/2020.07.09.194902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural inventory of native ribosomal ABCE1-43S pre-initiation complexes

Abstract: In eukaryotic translation, the termination and recycling phases are linked to subsequent initiation by persistence of several factors. These comprise the large eIF3 complex, eIF3j (Hcr1 in yeast) and the ATP-binding cassette protein ABCE1 (Rli1 in yeast). The ATPase is mainly active as a recycling factor, but it can remain bound to the dissociated 40S subunit until formation of 43S pre-initiation complexes. However, its functional role and native architectural context remains largely enigmatic. Here, w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 105 publications
4
13
0
Order By: Relevance
“…Indeed, eIF3J is less enriched than the core eIF3 complex in AP-MS, suggesting a preference for inhibiting open head conformations. The marked enrichment of the ABC-type ATPase ABCE1, found in some eIF3J-bound 43S states ( 34 ) is consistent with the presence of this factor in Nsp1-bound ribosomes ( 10 ).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Indeed, eIF3J is less enriched than the core eIF3 complex in AP-MS, suggesting a preference for inhibiting open head conformations. The marked enrichment of the ABC-type ATPase ABCE1, found in some eIF3J-bound 43S states ( 34 ) is consistent with the presence of this factor in Nsp1-bound ribosomes ( 10 ).…”
Section: Discussionsupporting
confidence: 63%
“…Our model is consistent with results that indicate a competition between Nsp1 and eIF3J binding to the ribosome ( 25 ). In eIF3J-bound, closed head conformations ( 34 ), the space occupied by the Nsp1 NTD in our main cluster of models clashes with the locked rRNA (Fig. S10).…”
Section: Discussionmentioning
confidence: 96%
“…Consistent with this, recent studies showed that yeast lacking eIF3j exhibits a defect in ribosome recycling similar to that observed in the strain depleted of Rli1 [ 42 ] and eIF3j improves the efficiency of subunit splitting by Rli1 in a reconstituted assay. [ 43 ] These data establish that eIF3j is important for enhancing the recycling activity of Rli1/ABCE1 and are consistent with the observation that eIF3j physically interacts with Rli1 by yeast two‐hybrid analysis. [ 25,44 ] In particular, cryo‐EM structures showed that the N‐terminus of eIF3j binds to the cleft between NBD1 and NBD2 of Rli1/ABCE1 [ 43,45 ] and could therefore directly modulate the ATPase activity of Rli1/ABCE1 (Figure 2B, inset).…”
Section: The Molecular Mechanism Of Ribosome Recyclingsupporting
confidence: 84%
“…[ 43 ] These data establish that eIF3j is important for enhancing the recycling activity of Rli1/ABCE1 and are consistent with the observation that eIF3j physically interacts with Rli1 by yeast two‐hybrid analysis. [ 25,44 ] In particular, cryo‐EM structures showed that the N‐terminus of eIF3j binds to the cleft between NBD1 and NBD2 of Rli1/ABCE1 [ 43,45 ] and could therefore directly modulate the ATPase activity of Rli1/ABCE1 (Figure 2B, inset).…”
Section: The Molecular Mechanism Of Ribosome Recyclingsupporting
confidence: 83%
“…4d) and the clusters are prone to degradation by ROS 88 . Extensive structural and biochemical studies have yielded molecular insight into the role of the [FeS] cluster domain in ribosome recycling [89][90][91][92][93][94][95][96] . Briefly, upon ATP binding to both sites in ABCE1, the protein undergoes a conformational switch from an open to a closed ATP-occluded state, which drives ribosome dissociation (Fig.…”
Section: Iron-sulfur Clusters As Inhibitors and Catalysts Of Viral Re...mentioning
confidence: 99%